The effectiveness of integrative couple therapy on the quality of marital relationships and cognitive regulation of emotions in incompatible couples - Mousavi Diva, Sayedeh Raziyeh; Haydari, Shaban; Ghanadzadegan, Hossein Ali (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to compare the effectiveness of integrative couple therapy on the quality of marital relationships and cognitive regulation of emotions in incompatible couples. Methods: The current research was a semi-experimental type with a pre-test-post-test design with a control group. The statistical population included all the couples who referred to the counseling centers of Amol city during March 2021, who referred because of incompatibility or the psychologists of the center identified the cause of the conflict as incompatibility. The sample size, the number of 20 couples (40 people) (10 couples for the experimental group and another 10 couples for the control group) from the entire statistical population, the cluster sampling method was used, and finally, with this method, five centers were used to select the samples. The training sessions of the integrative couple therapy group were implemented using Christensen and Jacobson’s (2000) integrative couple therapy. The questionnaires of the study were Busby et al.’s Marital Relationship Questionnaire (1995) and Garnefski et al.’s (2001) Emotion Regulation Questionnaire. Findings were analyzed using repeated measures with a mixed design. Results: The results of the research showed that the results showed that integrative couple therapy training increases the quality of marital relationships (P<0.001, F = 46.30) and positive emotional cognitive regulation (P< 0.001, F=62.35) and negative (P<0.001, F=137.80) has been effective. Conclusion: Therefore, it can be concluded that integrative couple therapy was effective in improving the quality of marital relations and cognitive adjustment of incompatible couples.